A Critical Review of Morphologic Findings and Data From 14 Toxicological Studies Involving Fish Exposures to Diclofenac. (July 2021) - Wolf, Jeffrey C.
A number of studies have investigated the potential toxicity of the analgesic agent diclofenac (DCF) in various fish species under a diverse array of experimental conditions. Reported evidence of toxicity in these investigations is often strongly reliant on morphologic end points such as histopathology, immunohistochemistry, and transmission electron microscopy. However, it may be challenging for scientists who perform environmental hazard or risk determination to fully appreciate the intricacies of these specialized endpoints. Therefore, the purpose of the current review was to critically assess the quality of morphologic data in 14 papers that described the experimental exposure of fish to DCF. Areas of focus during this review included study design, diagnostic accuracy, magnitude of reported changes, data interpretation and presentation, and the credibility of individual reported findings. Positive attributes of some studies included robust experimental designs, accurate diagnoses, and straightforward and transparent data reporting. Issues identified in certain articles included diagnostic errors, failure to account for sampling and/or observer bias, failure to evaluate findings according to sex, exaggeration of lesion severity, interstudy inconsistencies, unexplained phenomena, and incomplete or ambiguous data presentation. It is hoped that the outcome of this review will be of value for personnel involved in regulatory decision-making.